A Softwaremodule for an Ethical Elder Care Robot. Design and Implementation - Misselhorn, Catrin (ETHICS IN PROGRESS, 2019)
The development of increasingly intelligent and autonomous technologies will eventually lead to these systems having to face morally problematic situations. This is particularly true of artificial systems that are used in geriatric care environments. The goal of this article is to describe how one can approach the design of an elder care robot which is capable of moral decision-making and moral learning. A conceptual design for the development of such a system is provided and the steps that are necessary to implement it are described.